2022
DOI: 10.24012/dumf.1096691
|View full text |Cite
|
Sign up to set email alerts
|

Using machine learning algorithms for classifying transmission line faults

Abstract: The faults in transmission lines should be identified for attaining high quality energy in electrical power systems. Savings can be made in both time and energy if the transmission line faults are classified accurately. The present study examined phase-ground, phase-phase-ground, phase-phase, phase-phase-phase and no fault cases. Support Vector Machine (SVM), K-Nearest Neighbours Algorithm (KNN), Decision Tree (DT), Ensemble, Linear discriminant analysis (LDA) classifiers were used for classifying the transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Another strategy in machine learning is to use ensemble classifiers [9]. These techniques use several learning algorithms so that they can produce more accurate models and avoid overfitting [43].…”
Section: Bsdt For Fault Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another strategy in machine learning is to use ensemble classifiers [9]. These techniques use several learning algorithms so that they can produce more accurate models and avoid overfitting [43].…”
Section: Bsdt For Fault Classificationmentioning
confidence: 99%
“…Tree-based ensemble techniques are commonly used for classification and regression in many research fields [7], [8]. Two such tree-based ensemble techniques are the Boosted Decision Tree (BSDT) for classification [9] and bagged decision tree for regression problems [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated the effectiveness of various ML approaches, including artificial neural networks (ANNs), support vector machines (SVMs), decision trees, and ensemble methods, in analyzing electrical signals and identifying fault patterns. [2,3] For example, Li et al [4] utilized a deep learning-based approach for fault detection in power transmission systems, achieving high accuracy rates even in the presence of noise and disturbances. Similarly, Wong et al [5] proposed a hybrid machine learning model combining convolutional neural networks (CNNs) and long short-term memory (LSTM) networks for fault diagnosis in power systems, showcasing significant improvements in fault detection performance compared to traditional methods.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a surge in research exploring the application of machine learning algorithms for transmission line fault detection [1]. Studies have demonstrated the effectiveness of various ML approaches, including artificial neural networks (ANNs), support vector machines (SVMs), decision trees, and ensemble methods, in analyzing electrical signals and identifying fault patterns [2,3].…”
Section: Introductionmentioning
confidence: 99%